Role of preeclampsia-related angiogenic factors in sunitinib cardiotoxicity: two cases and review of the literature. (January 2013) - Gallucci, Giuseppina; Tartarone, Alfredo; Tocchetti, Carlo Gabriele; Bochicchio, Anna Maria; Coccaro, Mariarosa; Capobianco, Alba; Maurea, Nicola; Improta, Giuseppina; Zupa, Angela; Aieta, Michele
Sunitinib is a multi-targeted tyrosine kinase inhibitor widely used in clear cell renal carcinoma and in imatinib-resistant gastrointestinal stromal tumors. Sunitinib-associated cardiotoxicity has been recognized and includes hypertension, left ventricular dysfunction and congestive heart failure; nevertheless, few data exist in the literature regarding the role of preeclampsia-related angiogenic factors in sunitinib cardiotoxicity. We report a case of sunitinib-induced severe left ventricular dysfunction that occurred in a hypertensive woman with metastatic renal carcinoma and a history of preeclampsia, and a case of sunitinib-induced preeclampsia-like syndrome in a normotensive patient with an imatinib-resistant gastrointestinal stromal tumor. Our experience confirms that inhibition of angiogenic factors to treat cancer is a novel challenge for the oncologist and requires the cardiologist's support.